2009
DOI: 10.1189/jlb.0908560
|View full text |Cite
|
Sign up to set email alerts
|

IFN-α amplifies human naïve B cell TLR-9-mediated activation and Ig production

Abstract: TLRs are a family of molecules that function as sensors for the detection of pathogens. TLR-9, expressed on B cells and pDCs, recognizes CpG motifs of unmethylated bacterial DNA and plays a role in the development of autoimmunity. The present study was designed to investigate the effects of IFN-alpha in combination with CpG ODN on the activation of CD27(-) naïve B cells and on Ig production. We provide evidence that CpG ODN not only induces a total and T-dependent, specific IgM response by naïve B cells but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 39 publications
3
46
0
Order By: Relevance
“…Such nucleic acid-containing immunocomplexes were shown to activate autoreactive B cells and autoantibody production. TLR-9-active sequence transgenic mice produce large amounts of anti-RNA, -DNA and -nucleosome antibodies of the IgG2a and IgG2b isotype that cause nephritis [27]. B cells can promptly detect and mount responses to antigen after immunization.…”
Section: Discussionmentioning
confidence: 99%
“…Such nucleic acid-containing immunocomplexes were shown to activate autoreactive B cells and autoantibody production. TLR-9-active sequence transgenic mice produce large amounts of anti-RNA, -DNA and -nucleosome antibodies of the IgG2a and IgG2b isotype that cause nephritis [27]. B cells can promptly detect and mount responses to antigen after immunization.…”
Section: Discussionmentioning
confidence: 99%
“…40 Recent report has described CD38 upregulation and differentiation of B cells in plasma cells after stimulation with CpG ODN. 41 We show that the expression of CD38 on B-CLL cells could be induced by 2 mechanisms. Either by the direct stimulation of B-CLL cells by agonists of TLR-7 and TLR-9, receptors expressed on B-CLL cells.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…Immunohistochemical and molecular studies have shown that transcriptionally active CD138+ plasma cells -that have undergone affinity maturation and switched their isotype from IgM to IgG or IgA -are abundant in PM muscle (Greenberg, 2007a;Salajegheh et al, 2010b;Cappelletti et al, 2011). In view of the recently demonstrated ability of TLR9 to induce B cells to mature to plasma cell in vitro (Giordani et al, 2009), together with the observed upregulation of TLR9 in this form of myopathy , it is reasonable to hypothesize a role for this receptor in immunoglobulin production in PM.…”
Section: Cytokines Chemokines and Activation Of The Innate Immune Rementioning
confidence: 99%